Introduction to the themed issue 'The health benefits of UV radiation exposure through vitamin D production or non-vitamin D pathways'. Issue 3 (3rd February 2017) - Hart, Prue H.; Norval, Mary; Reeve, Vivienne E.
Abstract : Sun exposure stimulates vitamin D production in addition to several immunomodulatory pathways. Fifteen perspectives in this themed issue aim to distinguish the contribution of vitamin D-dependent and independent pathways, initiated by UV radiation exposure, to beneficial health outcomes.